Synthesis and properties of five ring fused aromatic compounds based on S, S-dioxide benzothiophene. (25th January 2018) - Zhang, Yuhao; Peng, Feng; He, Ruifeng; Ying, Lei; Yang, Wei; Cao, Yong
Abstract : Asymmetrical five ring fused compounds based on S, S -dioxide benzothiophene, BTOF andBTOCz, have wide bandgaps and deep HOMO and LUMO levels. Abstract : Asymmetrical five ring fused compounds based on S, S -dioxide benzothiophene, 9, 9-dioctylfluorene[2, 3- b ]benzo[ d ]thiophene- S, S -dioxide(BTOF ) and N -(2-decyltetradecyl)carbazole[2, 3- b ]benzo[ d ]thiophene- S, S -dioxide (BTOCz ) were synthesized and characterized.BTOF andBTOCz were readily soluble in common organic solvents and exhibited high thermal stability with the melting points ( T m s) of 119 °C and 150 °C, and thermal decomposition temperatures ( T d s) of 280 °C and 338 °C, respectively. The highest occupied molecular orbital energy levels (HOMOs), the lowest unoccupied molecular orbital energy levels (LUMOs) and the band gaps ( E g s) ofBTOF andBTOCz were −6.11, −2.66 and 3.45 eV, −5.86, −2.52 and 3.34 eV, respectively. The photoluminescence (PL) spectra ofBTOF andBTOCz were peaked at 404 and 420 nm in film, and the photoluminescence quantum yields ( Q PL s) were 30% and 10% in toluene solution, respectively.BTOF andBTOCz showed strong intramolecular charge transfer (ICT) character, relatively high Q PL s and deeper HOMO and LUMO levels compared with compoundsBTF andBTCz . Compared with the symmetrical seven ring fused compounds FBTO and CzBTO, the asymmetrical five ring fused compoundsBTOF andBTOCz showed relatively shallow HOMO levels, which can facilitate hole injection, and therefore, could be potential construction units in organic semiconductors.